Code Switching and Code Mixing in Selling and Buying Interactions in Martapura Traditional Market - Sulistyo, Bambang; Nurulanningsih, Nurulanningsih; Darningwati, Darningwati; Ramadhaniati, Ratih Utami; Nurhasanah, Nurhasanah (Universitas Jambi, Indonesia, 2023)
This research aimed to describe linguistic phenomena, namely code switching and code mixing among sellers and buyers at the Martapura traditional market. This type of research was descriptive research that used theoretical and descriptive methods. It included planning and implementation research. The subjects in this research were sellers and buyers at the Martapura market. The data in this research were the language used by sellers and buyers in Martapura Market during buying and selling transactions. Therefore, free listening techniques, recording techniques, and note-taking techniques were used in conversations. The results showed that code-switching and code-mixing between sellers and buyers at the Martapura traditional market were caused by several factors, such as age, gender, and ethnicity. Almost all sellers and buyers who trade at the Martapura traditional market are native Javanese and Palembang people, so they automatically speak Javanese and Palembang languages.